Predictive Role of Serum Tumor Markers in Diagnosis of Pulmonary Tuberculosis - Jingjing MA; Dan XIA; Jing HU; Rui FU; Lijun XU; Ying ZHANG; Mengying ZHANG; Benhe LI; Jianghua YANG; Yufeng WEN (Tehran University of Medical Sciences, 2016)
Background: The diagnosis of pulmonary tuberculosis (PTB) is complicated and time-consuming currently. There was association of PTB with serum tumor markers. In this study we aimed to evaluate the predictive role of serum CA125, CA199 and CEA as diagnostic tools for PTB. Methods: This study was designed as a case-control study with 565 subjects who visited the Yijishan Hospital from Jun to Dec in 2014.This case-control study matched as for age and sex with 113 cases and 452 controls. Serum CA125, CA199 and CEA levels were detected by electrochemiluminescence instrument. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was performed to evaluate the diagnostic value on PTB. Results: Serum levels of CA125, CA199 and CEA in PTB patients were significantly higher than those in control group (P<0.001). There was no significantly different of three tumor markers between initial treatment group and retreatment group. The logistic regression analysis showed that CA125 was an impact factor to PTB. The ROC analysis revealed that AUC of CA125 was 0.966 (95%CI: 0.951-0.981), the sensitivity, specificity in serum and cut-off were 95.6%, 85.0% and 10.30 U/ml, respectively. Conclusion: The serum CA125 has potential good diagnostic performance for PTB.